Synthesis of olivine phase and chemical reactions between Mg–Si–O systems under shock compression. (July 2014) - Zhang, F.; Liu, Y.; Liu, G.; Du, J.; He, H.
<x content-type="archive" xml:space="preserve">Abstract</x> Shock synthesis experiments were conducted by using explosively accelerated flyer plate which impacted the containers. Starting materials in containers were 2MgO+SiO2 (stoichiometric ratio to form Mg2SiO4) or MgO+SiO2 (stoichiometric ratio to form MgSiO3) powder mixtures. The structures of the products were determined by X-ray diffraction (XRD). The yield of the olivine phase increases with the increase in impact pressure, when the peak pressure of the container reaches 94·4 GPa, a pure olivine phase was obtained. The MgSiO3 phase has not been observed and only the olivine phase has been observed when the starting material is 2MgO+SiO2. Even if the starting material is MgO+SiO2, the major phase is Mg2SiO4 and the XRD peak of MgSiO3 is not observed until the pressure reaches 94·4 GPa. A vibration theory is proposed to explain this kind of chemoselectivity.